HUBUNGAN STATUS GIZI DENGAN USIA MENARCHE SISWI SMP PGRI BENDO PARE KEDIRI - Nurul Laili; Farida Hayati (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
Nutrition status in women greatly affects the occurrence of menarche, especially from the age of menarche. Good nutrition status also affects the incidence of menarche because of the influence of substances consumed every day, especially carbohydrates and proteins. Nutrition affects sexual maturity. The objective of this study was to identify the relationship of nutrition status with age of menarche. The design used in this research is cross sectional. Population in this research is all student of PGRI Yunior High School Bendo Pare Kediri. The sample in this research is student of PGRI Yunior High School Bendo Pare Kediri that exist at the time of research in February 2017. Analysis conducted in this research by using Rank Spearman Correlation. Obtained a value of Rho = 0.233 which indicates the level of moderate relationship. Statistical test value t arithmetic = 4.68 greater than the value of t table = 2.539, then H₁ accepted and it can be concluded that there is a relationship between nutrition status with age menarche with the level of closenes.. The role of nutrition in regulating hormonal balance includes the hormones that regulate the female reproductive system. Fulfillment of nutrition needs makes the balance of nutrition in the body so it can affect the nutrition status. Nurses in providing nursing care through the School Health Unit can provide counseling about reproductive health, especially about menarche, factors that affect menarche delay and provide examples of how to meet the needs of good nutrition.